The white lions [videorecording (DVD)] - Kennedy, Joe; Moore, Toby Leonard (PBS Distribution, 2012)
The story of two remarkable and extremely rare white lion cubs on their journey to adulthood. Both are female, sisters born as white as snow in May 2009 in South Africa's Kruger Park.